DDRE-24. TARGETING PURINE METABOLISM TO OVERCOME GLIOBLASTOMA THERAPY RESISTANCE. (25th March 2021) - Zhou, Weihua; Yao, Yangyang; Scott, Andrew; Wilder-Romans, Kari; Dresser, Joseph; Werner, Christian; Sun, Hanshi; Pratt, Drew; Sajjakulnukit, Peter; Zaho, Shuang; Davis, Mary; Nelson, Barbara; et al.
Abstract: Intratumoral genomic heterogeneity in glioblastoma (GBM) is a barrier to overcoming radiation (RT) resistance. To discover genotype-independent mediators of RT resistance, we correlated RT resistance with the concentration of approximately 700 metabolites across 23 GBM cell lines. Purine metabolites, especially those containing the base guanine, were most correlated with RT resistance. Similarly, increased abundance of tumor purines was associated with decreased survival in GBM patients treated with RT. This relationship is causal. Purine supplementation protected RT-sensitive GBMs from RT and promoted the repair of RT-induced double strand DNA breaks (DSBs). In vitro and in vivo stable isotope tracing confirmed that GBM cell lines and orthotopic patient-derived xenografts primarily generated purines through the de novo synthetic pathway. RT treatment further increased de novo purine synthesis in GBM through signaling via the DNA damage response. Inhibition of de novo GTP synthesis with mycophenolic acid (MPA) sensitized multiple GBM cell lines and neurospheres to RT by slowing the repair of RT-induced DSBs. MPA-induced radiosensitization was GTP-dependent as it was rescued by nucleoside supplementation. Modulating pyrimidine metabolism affected neither RT resistance nor DSB repair, suggesting these GTP-specific effects are due to active signaling rather than its ability to act as a physical substrate for DNA repair and candidate signaling molecules have been identified. These results were recapitulated in vivo with mycophenolate mofetil (MMF), the orally bioavailable FDA-approved prodrug of MPA. MMF potentiated RT efficacy, reduced tumor guanylates and slowed the repair of RT-induced DSBs across multiple models. Because de novo purine synthesis is activated by many of the oncogenic alterations that drive GBM, its inhibition is a promising genotype-independent strategy to overcome GBM RT resistance. We have now begun a clinical trial to determine whether combining MMF and RT is safe and potentially efficacious in patients with GBM.